2009
DOI: 10.1007/s11751-009-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of distal tibial intra-articular fractures with circular external fixation

Abstract: The treatment of tibial plafond fractures requires careful management of the soft tissue envelope, reconstruction of the articular surface and stable fixation with minimal additional damage. Thirty cases of AO type 43 C tibial fractures were treated by transosseous osteosynthesis (Ilizarov technique). The external fixator constructs used were Ilizarov (Transosseous osteosynthesis: theoretical and clinical aspects of the regeneration and growth of tissue, Springer, Berlin, 1992) and Sheffield (Classification AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Several studies were carried out to compare intramedullary nailing to plating, plating to external fixation and intramedullary nailing to external fixation. 18,19 Various clinical studies have compared IMN and MIPO 20,21,22 the former leads to a lower rate of soft tissue complications and infections and has been associated with a significantly shorter full weight bearing and a shorter union time. On the other hand, IMN appears has been reported to lead to a higher rate of malunion and nonunion because it may involve reduction issues 23,24 The present study was conducted to evaluate the functional outcome of distal tibia extra articular fracture operated with IMN and MIPO.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were carried out to compare intramedullary nailing to plating, plating to external fixation and intramedullary nailing to external fixation. 18,19 Various clinical studies have compared IMN and MIPO 20,21,22 the former leads to a lower rate of soft tissue complications and infections and has been associated with a significantly shorter full weight bearing and a shorter union time. On the other hand, IMN appears has been reported to lead to a higher rate of malunion and nonunion because it may involve reduction issues 23,24 The present study was conducted to evaluate the functional outcome of distal tibia extra articular fracture operated with IMN and MIPO.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical studies have compared IMN and LP [ 13 , 20 22 ]: the former leads to a lower rate of soft tissue complications and infections and has been associated with a significantly shorter full weight bearing and a shorter union time. On the other hand, IMN appears has been reported to lead to a higher rate of malunion and nonunion because it may involve reduction issues [ 16 , 19 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as some authors showed that circular frames are associated with less bony or soft tissue complications compared to ORIF for type C pilon fractures. 8 – 11 …”
Section: Discussionmentioning
confidence: 99%